Shaping symmetric Airy beam through binary amplitude modulation for ultralong needle focus - Zhao Xiang, Fang (2015)
Needle-like electromagnetic field has various advantages for the applications in high-resolution imaging, Raman spectroscopy, as well as long-distance optical transportation. The realization of such field often requires high numerical aperture (NA) objective lens and the transmission masks. We demonstrate an ultralong needle-like focus in the optical range produced with an ordinary lens. This is achieved by focusing a symmetric Airy beam (SAB) generated via binary spectral modulation with a digital micromirror device. Such amplitude modulation technique is able to shape traditional Airy beams, SABs, as well as the dynamic transition modes between the one-dimensional and two-dimensional (2D) symmetric Airy modes. The created 2D SAB was characterized through measurement of the propagating fields with one of the four main lobes blocked by an opaque mask. The 2D SAB was verified to exhibit self-healing property against propagation with the obstructed major lobe reconstructed after a certain distance. We further produced an elongated focal line by concentrating the SAB via lenses with different NAs and achieved an ultralong longitudinal needle focus. The produced long needle focus will be applied in optical, chemical, and biological sciences.